A pragmatic randomized trial of a polypill-based strategy to improve use of indicated preventive treatments in people at high cardiovascular disease risk. (July 2015) - Patel, Anushka; Cass, Alan; Peiris, David; Usherwood, Tim; Brown, Alex; Jan, Stephen; Neal, Bruce; Hillis, Graham S; Rafter, Natasha; Tonkin, Andrew; Webster, Ruth; Billot, Laurent; et al.
Background: Most individuals at high cardiovascular disease (CVD) risk worldwide do not receive any or optimal preventive drugs. We aimed to determine whether fixed dose combinations of generic drugs ('polypills') would promote use of such medications. Methods: We conducted a randomized, open-label trial involving 623 participants from Australian general practices. Participants had established CVD or an estimated five-year CVD risk of ≥15%, with indications for antiplatelet, statin and ≥2 blood pressure lowering drugs ('combination treatment'). Participants randomized to the 'polypill-based strategy' received a polypill containing aspirin 75 mg, simvastatin 40 mg, lisinopril 10 mg and either atenolol 50 mg or hydrochlorothiazide 12.5 mg. Participants randomized to 'usual care' continued with separate medications and doses as prescribed by their doctor. Primary outcomes were self-reported combination treatment use, systolic blood pressure and total cholesterol. Results: After a median of 18 months, the polypill-based strategy was associated with greater use of combination treatment (70% vs . 47%; relative risk 1.49, (95% confidence interval (CI) 1.30 to 1.72) p < 0.0001; number needed to treat = 4.4 (3.3 to 6.6)) without differences in systolic blood pressure (−1.5 mmHg (95% CI −4.0 to 1.0) p = 0.24) or total cholesterol (0.08 mmol/l (95% CI −0.06 to 0.22) p = 0.26). At study end, 17% and 67% of participants in polypill and usual care groups, respectively, were taking atorvastatin or rosuvastatin. Conclusion: Provision of a polypill improved self-reported use of indicated preventive treatments. The lack of differences in blood pressure and cholesterol may reflect limited study power, although for cholesterol, improved statin use in the polypill group counter-balanced use of more potent statins with usual care.